Reducing the Cost of Laparoscopy: Reusable versus Disposable Laparoscopic Instruments. (22nd July 2014) - Manatakis, Dimitrios K.; Georgopoulos, Nikolaos
Abstract : Cost-effectiveness in health care management is critical. The situation in debt-stricken Greece is further aggravated by the financial crisis and constant National Health System expense cut-downs. In an effort to minimize the cost of laparoscopy, our department introduced reusable laparoscopic instruments in December 2011. The aim of this study was to assess potential cost reduction of laparoscopic operations in the field of general surgery. Hospital records, invoice lists, and operative notes between January 2012 and December 2013, were retrospectively reviewed and data were collected on laparoscopic procedures, instrument failures, and replacement needs. Initial acquisition cost of 5 basic instrument sets was €21, 422. Over the following 24 months, they were used in 623 operations, with a total maintenance cost of €11, 487. Based on an average retail price of €490 per set, projected cost with disposable instruments would amount to €305, 270, creating savings of €272, 361 over the two-year period under study. Despite the seemingly high purchase price, each set amortized its acquisition cost after only 9 procedures and instrument cost depreciated to less than €55 per case. Disposable instruments cost 9 times more than reusable ones, and their high price would almost equal the total hospital reimbursement by social security funds for many common laparoscopic procedures.